Strategi Branding Dalam Meningkatkan Kepercayaan Masyarakat Terhadap Madrasah Tsanawiyah Negeri - Karsono Karsono; Purwanto Purwanto; Abdul Matin Bin Salman (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the branding strategy at MTsN Purbalingga Regency and to determine the level of effectiveness of branding management strategies at MTsN Purbalingga Regency in 2018 to 2020. This study uses a qualitative descriptive method. This method is used to describe and analyze branding management strategies at MTsN in Purbalingga Regency and describe user responses to branding management strategies at MTsN Purbalingga Regency. The places chosen to conduct the research were MTsN 01 Purbalingga, MTsN 02 Purbalingga, and MTsN 03 Purbalingga. Informants from this research are principals, teachers, staff, and students. Then to select and determine the informants in this study, the researchers used a purposive sampling technique. Data collection techniques in this research are using content/document analysis techniques, in-depth interviews, and events/observations. The method used to check the validity of the data is the triangulation method. The data analysis technique used in this research is interactive model analysis. The stages in analyzing the data in this study are data reduction, data presentation, and conclusion drawing. The results showed that: 1). the branding strategies that have been carried out by MTsN in Purbalingga Regency between one MTsN and other MTsN are the same and some are different, this of course depends on the branding management carried out by each school. MTsN 1 Purbalingga, namely by improving the quality both in terms of achievement and non-academic namely character building, MTs Negeri 2 Purbalingga emphasizes efforts to attract interest in terms of performance and community service, while MTs Negeri 3 Purbalingga in an effort to attract interest by achieving good academic achievements and non-academic and performance services for both teachers and employees; 2). The effectiveness of the branding strategy carried out at MTs Negeri Purbalingga Regency in 2018 to 2020 is quite effective in increasing public trust.